Mice lacking Gpr37 exhibit decreased expression of the myelin-associated glycoprotein MAG and increased susceptibility to demyelination. (1st September 2017) - Smith, Brilee M.; Giddens, Michelle M.; Neil, Jessica; Owino, Sharon; Nguyen, TrangKimberly T.; Duong, Duc; Li, Fengqiao; Hall, Randy A.
Highlights: Myelin-associated glycoprotein expression is lower in brains of mice lacking GPR37. Loss of GPR37 results in increased susceptibility to demyelination. GPR37 is identified as a target for understanding and treating demyelination. Abstract: GPR37 is an orphan G protein-coupled receptor that is predominantly expressed in the brain and found at particularly high levels in oligodendrocytes. GPR37 has been shown to exert effects on oligodendrocyte differentiation and myelination during development, but the molecular basis of these actions is incompletely understood and moreover nothing is known about the potential role(s) of this receptor under demyelinating conditions. To shed light on the fundamental biology of GPR37, we performed proteomic studies comparing protein expression levels in the brains of mice lacking GPR37 and its close relative GPR37-like 1 (GPR37L1). These studies revealed that one of the proteins most sharply decreased in the brains of Gpr37/Gpr37L1 double knockout mice is the myelin-associated glycoprotein MAG. Follow-up Western blot studies confirmed this finding and demonstrated that genetic deletion of Gpr37, but not Gpr37L1, results in strikingly decreased brain expression of MAG. Further in vitro studies demonstrated that GPR37 and MAG form a complex when expressed together in cells. As loss of MAG has previously been shown to result in increased susceptibility to brain insults, we additionally assessed Gpr37 -knockout ( Gpr37 − / − ) vs. wild-type mice in the cuprizone model of demyelination. These studies revealed that Gpr37 − / − mice exhibit dramatically increased loss of myelin in response to cuprizone, yet do not show any increased loss of oligodendrocyte precursor cells or mature oligodendrocytes. These findings reveal that loss of GPR37 alters oligodendrocyte physiology and increases susceptibility to demyelination, indicating that GPR37 could be a potential drug target for the treatment of demyelinating diseases such as multiple sclerosis.